2020
DOI: 10.1161/strokeaha.119.028718
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of Targeting a LDL (Low-Density Lipoprotein) Cholesterol <70 mg/dL During 5 Years After Ischemic Stroke

Abstract: Background and Purpose— The TST trial (Treat Stroke to Target) evaluated the benefit of targeting a LDL (low-density lipoprotein) cholesterol of <70 mg/dL to reduce the risk of cardiovascular events in 2860 patients with ischemic stroke with atherosclerotic stenosis of cerebral vasculature or aortic arch plaque >4 mm, in a French and Korean population. The follow-up lasted a median of 5.3 years in French patients (similar to the median follow-up time in the SPARCL trial [Stroke Prevention by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 21 publications
1
17
0
2
Order By: Relevance
“…The primary composite endpoint occurred in 121 (8.5%) and 156 (10.9%) participants, respectively (adjusted HR, 0.77; 95% CI, 0.61 to 0.98; P=0.035). Similar results were obtained when French participants were analyzed separately; 7 the primary endpoint occurred in 9.6% and 12.9% of the participants, respectively (HR, 0.74; 95% CI, 0.57 to 0.94; P=0.019). Myocardial infarction or urgent coronary revascularization occurred in 1.7% and 2.5% of the participants, respectively (HR, 0.66; 95% CI, 0.37 to 1.20; P=0.…”
Section: Introductionsupporting
confidence: 78%
“…The primary composite endpoint occurred in 121 (8.5%) and 156 (10.9%) participants, respectively (adjusted HR, 0.77; 95% CI, 0.61 to 0.98; P=0.035). Similar results were obtained when French participants were analyzed separately; 7 the primary endpoint occurred in 9.6% and 12.9% of the participants, respectively (HR, 0.74; 95% CI, 0.57 to 0.94; P=0.019). Myocardial infarction or urgent coronary revascularization occurred in 1.7% and 2.5% of the participants, respectively (HR, 0.66; 95% CI, 0.37 to 1.20; P=0.…”
Section: Introductionsupporting
confidence: 78%
“…A previous study demonstrated that strict LDL-C control by rosuvastatin might stabilize atheromatous aortic plaques in acute ischemic stroke patients with large plaques ≥ 4 mm thick on TEE 33) . A recent trial, which evaluated the benefit of aggressive LDL-C control (LDL-C 70 mg/dL) via basal control with statins, reported a significant reduction of major cardiovascular events in patients with ischemic stroke and atherosclerotic disease including aortic arch plaques ≥ 4 mm in thickness 34) . These data suggest that in addition to oral anticoagulant, statin therapy may be a secondary prevention option for these patients.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the SPARCL study showed that lipid-lowering therapy reduced stroke recurrence in patients who achieved normal blood lipid levels (27). Recently, the TST trial demonstrated that targeting a LDL-C level <70 mg/dL (1.8 mmol/L) for 5.3 years avoided 25% of subsequent vascular events and ischemic stroke without increasing the risk of intracranial hemorrhage (8). These findings suggested that lowering LDL-C could further address the residual risks in patients with ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies have shown that elevated LDL and reduced HDL levels increase the risk of stroke (7). The Treat Stroke to Target (TST) trial evaluated the benefit of dyslipidemia management and showed that targeting a LDL cholesterol level <70 mg/dL after a recent ischemic stroke or TIA could significantly decrease the occurrence of cardiovascular events, cerebral infarction, and recurrent cerebral infarction or hemorrhage as compared with targeting a LDL cholesterol of 100 ± 10 mg/dL (8). However, consistent conclusions have not been reached regarding pharmacological interventions that raise HDL-C concentrations (7).…”
Section: Introductionmentioning
confidence: 99%